KOT YIKAMA ATIK SUYUNUN MEMBRAN TEKNOLOJİLERLE GERİ KAZANILABİLİRLİĞİ - ARIN, MERVE (Fırat Üniveristesi, 2011)
Atıksuyun arıtılarak yeniden kullanılması dünyada yaygın bir uygulama haline gelmiştir. Atıksuyun arıtılmasıyla doğadaki su döngüsü kısaltılarak su kaynakları korunmuş ve su ihtiyacı karşılanmış olur. İleri arıtma tekniklerinden biri olan membran prosesler ile kirlenmiş su çok iyi kalitede geri kazanılabilmektedir.Bu çalışmada MF ve TO gibi membran proseslerle kot yıkama atıksuyunun arıtılabilirliği incelenmiştir. Deneysel çalışmalar esnasında pH, iletkenlik, absorbans, TKM, KOİ analizlenmiş ve ürün suyunun hacmi belirlenmiştir. Deneyler süresince giriş-çıkış basınçları ve akılar izlenmiştir. Akının azalması ve TO membranının tıkanması sonucu kimyasal yıkama yapılmış, tekrar atıksu ile çalışılmaya başlanmıştır.Kot yıkama atıksuyunun iletkenlik değeri 0,4-2,7 mS/cm arasında değişirken, iletkenlik giderimi MF ile yüzde 2, TO ile yüzde 99 civarında olmuştur. Renk analizi esnasında en yüksek absorbansa sahip 660 nm' lik dalga boyu kullanılmıştır. Renk MF ile yüzde 10, TO ile yüzde 100 giderilmiştir. TKM giderimi; MF ile yüzde 8, TO ile yüzde 97 olmuştur. Ham atıksu 1000-5050 mg/lt KOİ değerine sahipken; KOİ, MF ile yüzde 9, TO ile yüzde 100 civarında giderilmiştir.TO sisteminde ürün suyunun miktarı da farklı işletme basınçlarında belirlenmiştir. 10, 11, 12 atm' lik basınçlarda sırasıyla yüzde 7, yüzde 11 ve yüzde 93-100' lük ürün suyu dönüşümü sağlanmıştır.

The reuse of wastewater is being a common application over the world after reclaimed. By using the reclaimed wastewater, the period for hydrological recycle is shorted and the water resources are protected. The membrane processes as the advanced treatment methods can purify the wastewater to obtain high quality-effluent.In this study, the treatability of the rinsing effluent by membrane processes such as microfiltration (MF) and reverse osmosis (RO) was investigated. The parameters such as pH, conductivity, absorbance, TSM, COD during the experimental studies were analyzed and recovery volume of permeate was determined. During experiments, pressures and fluxes were continuously monitored. The membranes were washed by chemical reagents after fouling the membrane, and re-used.While the conductivity of rinsing effluent had the values between 0.4 mS/cm and 2.7 mS/cm, removal of conductivity has been around 2 % and 99 % by MF and RO, respectively. The wavelength with 660 nm during color analysis was used because it was the wavelength having maximum absorbance. The color was removed around 10 % and 100 % by MF and RO, respectively. Removal of TSM has been around 8 % and 97 % by MF and TO, respectively. The raw wastewater had ranged COD values between 1000 and 5050 mg/l, the COD was removed around 9 % and 100 % by MF and RO, respectively.The variation of permeate volume in RO system was also determined at the different operating pressures. It was obtained the permeate recovery of 7, 11 and 93-100 % at pressures with 10, 11 and 12 atm, respectively.
Recycling of wastewater used in washing jeans with membrane technologies
Keywords: Çevre Mühendisliği